Virtual decomposition controller for flexible-joint robot manipulators with non-full-state feedback. (15th December 2017) - Liu, Huashan; Li, Sheng; Wang, Baoxiang
In this article, a tracking controller for flexible-joint robot manipulators with non-full-state feedback is investigated based on virtual decomposition control (VDC) theory. First, virtual decomposition principle is applied to decouple the entire system of flexible-joint robot manipulator into rigid-link subsystems and flexible-joint subsystems; then, subcontrollers are designed correspondingly for each link or joint subsystem. Importantly, to realize the closed-loop tracking control without state measurements on the link side, an extended Kalman filter is designed to achieve the proposed VDC approach via non-full-state feedback. In addition, strict stability analysis of the control system is given according to the theory of virtual stability and Lyapunov stability. Finally, validation example is provided to verify the proposed control approach.